RICE FARMERS FACING CLIMATE CHANGE BY OPTIMIZING TECHNOLOGY ADOPTION BASE ON DIFFERENT LAND TYPOLOGIES - Yamin, Muhammad; Rejo, M. Amin; Mulyana, Eka (Faculty of Animal and Agricultural Science, Diponegoro University, 2025)
Climate change, such as flooding, is indeed a major challenge for the agricultural sector. However, farmers continue to try to overcome this impact by increasing the use of agricultural technology.The objectives of this research are (1) analyzing farmers' perceptions and levels of adoption of rice productivity in three land typologies, namely lowland swamp, tidal and rainfed land in South Sumatra, (2) analyzing the influence of socio-economic characteristics on the level of technology adoption, (3) rational behavior of farmers in dealing with floods as an impact of climate change (4) adaptation strategies for facing climate change. The sampling method used was a simple random sampling. The population of rice farmers is 854 farmers. By using the slovin method (α=0.1), 90 sample farmers were obtained. Data was collected through deep interviews in three regency in South Sumatera. Data processing uses are simultaneous multiple correlation test with SPSS software for the influence of socio-economic, KMO (Kaiser-Meyer-Olkin) method and Bartlett's test for testing rational behavior of farmers, and SWOT analysis for adaptation strategies. The research results show that farmers have adopted technology in the form of tractors, organic fertilizer, inorganic fertilizer, pesticides, combine harvesters, superior variety seeds, and rice threshing machines. The adoption rate in three regency of South Sumatra is in the high category, there is a relationship between perception and adoption level on productivity. On land with a lowland swamps and tidal lowland typology, farmers are more likely to pay attention to the technology used during irrigation and harvesting. Meanwhile, the typology of rainfed swamps includes planting methods and superior variety seeds. Tthe success of farming on three different technology is very dependent on proper irrigation using a system of opening and closing sluice gates. Therefore, for rainfed land, a water management system must be implemented to deal with the impacts of climate change.